Effects of Two Polysaccharides From Traditional Chinese Medicines on Rat Immune Function - Wang, Yu Lei; Shu, Xiang Hua; Zhang, Xue; Liu, Yong Bo; Zhang, Ya Jing; Lv, Tao; Huang, Xin; Song, Chun Lian (Frontiers in Veterinary Science, 2021)
To study the immune function effect of two polysaccharides extracted from traditional Chinese herbs on rats. Ultrasonic assisted extraction was used to extract the polysaccharide from traditional Chinese medicine. MTT assay was used to determine the effects of two polysaccharides on the conversion of pig peripheral T lymphocytes. 24 SD rats were selected for clinical trial, and divided into group B (blank group), group CK (cyclophosphamide inhibitory control group), group AP (angelica polysaccharide group) and group RIP (radix isatidis polysaccharide group). Except the group B, other groups can induce the immunodeficiency by using cyclophosphamide. Rats of AP group and RIP group were given gavage of 1mL of angelica polysaccharide (AP) and radix isatidis polysaccharide (RIP). The blood was sampled from the eyeball on day 0, 7, 14, 21, 28 and 35, respectively, to determine immune cells, IgG and IgM of immunoglobulin, body weight and spleen index. Results: The average content of AP and RIP was 51.27% and 14.8%, and the extraction rate was 75.23% and 60.94%. The maximum stimulation index (SI) was 1.407 when the concentration of AP was 8000 μg mL-1, and 1.5 when the concentration of RIP was 125 μg mL-1. Both two kinds of polysaccharides can alleviate the decline of white blood cells, lymphocytes, monocytes, neutrophils and serum IgG and IgM caused by cyclophosphamide. The two polysaccharides can regulate the rapid recovery of weight in immunosuppressed rats and increase the spleen index of immunosuppressed SD rats. The polysaccharides from the two traditional Chinese medicines can alleviate the immunosuppression caused by cyclophosphamide and promote the immune function of the body, which can be used as raw material resources of new veterinary medicine.